2023
DOI: 10.36312/jolls.v3i1.1178
|View full text |Cite
|
Sign up to set email alerts
|

Developing Islamic Tasks-Based Speaking English Materials for Islamic Elementary School Students: A Case Study at Elementary Schools in West Lombok, Indonesia

Bidari Andaru Widhi,
Jupri Jupri,
Jumadil Jumadil

Abstract: The present study aims to develop English Speaking Materials specifically designed for Islamic Elementary School students that adequately meet their language learning needs and preferences. In this regard, the study employs a Research and Development (R&D) ADDIE model, comprising five stages: analysis, design, development, implementation, and evaluation. The researcher not only acted as a materials developer but also as a teacher, since the data collection was conducted in the Islamic Elementary School. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Similarly, the teachers acknowledged the benefits of the joke approach in enhancing the students' speaking skills. They observed that the use of jokes during the language learning process made the sessions more enjoyable and interactive (Widhi et al, 2023;Hamidi et al, 2022). The teachers noted that the jokes helped create a relaxed and positive learning environment, which encouraged the students to actively participate and engage in conversations.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the teachers acknowledged the benefits of the joke approach in enhancing the students' speaking skills. They observed that the use of jokes during the language learning process made the sessions more enjoyable and interactive (Widhi et al, 2023;Hamidi et al, 2022). The teachers noted that the jokes helped create a relaxed and positive learning environment, which encouraged the students to actively participate and engage in conversations.…”
Section: Resultsmentioning
confidence: 99%
“…This academic paragraph explores the potential benefits of implementing such an integrated approach within Islamic-affiliated schools, where learners are empowered to take charge of their learning processes and enhance their academic achievement. By embracing self-regulated learning principles, learners at Islamic-affiliated schools can develop a deeper understanding of their individual learning needs and preferences, leading to increased engagement and motivation in the learning process (Karya et al, 2022;Widhi et al, 2023). The cultivation of self-confidence in communication and linguistic awareness further strengthens learners' abilities to actively participate in speaking and listening activities, fostering a conducive learning environment.…”
Section: Introductionmentioning
confidence: 99%
“…Speaking skills play a crucial role in enabling learners to effectively communicate in the target language (Hamidi et al, 2022;Hidayatullah & Haerazi, 2022). The development of speaking skills involves various interconnected components that contribute to a learner's ability to express themselves fluently, accurately, and appropriately (Assauri et al, 2022;Widhi et al, 2023). The key components of speaking skills in EFL contexts include pronunciation, vocabulary, fluency, and grammar (Kinasih & Olivia, 2022;Milanrianto et al, 2023).…”
Section: Introductionmentioning
confidence: 99%